PENGARUH PENERAPAN MODEL PROBLEM BASED LEARNING TERHADAP KEMAMPUAN MEMBACA PEMAHAMAN UNTUK MENGEMBANGKAN NILAI DISIPLIN SISWA SEKOLAH DASAR - Arkanjela Girlani Odang; Dyah Lyesmaya (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study was motivated by low reading comprehension scores and teaching methods that remain conventional. The objective of this study is to determine the extent of the influence of the problem-based learning model on the reading comprehension skills of fifth-grade students at SDN 10 PAMURUYAH. The research method used was quantitative with an experimental design. The research population included all fifth-grade students at SDN 10 PAMURUYAH, with the sample selected using purposive sampling. The instrument used was a reading comprehension test,and data collection was conducted via pretest and posttest. Data analysis was performed descriptively and using a paired-sample t-test to determine the significance of the effect of the problem-based learning model on reading ability. The results of this study indicate an increase from a pretest average score of 58.65 to 74.35 on the posttest. The results of the paired-sample t-test showed a significance level of <0.005, indicating that the problem-based learning model is capable of improving reading comprehension among fifth-grade students at SDN 10 PAMURUYAH